2019
DOI: 10.1007/s00380-019-01516-9
|View full text |Cite
|
Sign up to set email alerts
|

Different vascular healing process between bioabsorbable polymer-coated everolimus-eluting stents versus bioresorbable vascular scaffolds via optical coherence tomography and coronary angioscopy (the ENHANCE study: ENdothelial Healing Assessment with Novel Coronary tEchnology)

Abstract: Recent clinical trials have raised concerns about the safety and efficacy of ABSORB™ bioresorbable vascular scaffolds (BVS). The difference in the vascular healing process between SYNERGY™ bioabsorbable polymer-coated everolimus-eluting stents (BP-EES) and BVS remains unclear. The aim of the ENHANCE study was to compare vascular healing on BP-EES versus BVS by optical coherence tomography (OCT) and coronary angioscopy (CAS) at 4-and 12-month follow-ups. This is a prospective, non-randomized, single center clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Dissection, untreated stenosis and untreated lipid-rich plaque in the stent edge segment are associated with an increased risk of adverse clinical events such as stent thrombosis and edge restenosis. [10][11][12] Although clinical Fig. 3 Definitions of lesion and stent segment.…”
Section: Discussionmentioning
confidence: 99%
“…Dissection, untreated stenosis and untreated lipid-rich plaque in the stent edge segment are associated with an increased risk of adverse clinical events such as stent thrombosis and edge restenosis. [10][11][12] Although clinical Fig. 3 Definitions of lesion and stent segment.…”
Section: Discussionmentioning
confidence: 99%
“…Only Feng et al in 2013 showed evidence of inflammation at 3–6 months. When compared to CrCo stents, Iron-based stents exhibited good and homogeneous reendothelialization [ 95 ] contrary to first and second generation polymer-based resorbable stents which prolongated neointimal healing and were suspected to cause higher rate of thrombosis compared to drug eluting stents [ 96 , 97 ]. All these works found brownish deposits around struts, which are products of iron degradation.…”
Section: Biosafety Of Fe-based Stentmentioning
confidence: 99%